Circulating tumor DNA in advanced solid tumors: Clinical relevance and future directions. (9th November 2020) - Cheng, Michael L.; Pectasides, Eirini; Hanna, Glenn J.; Parsons, Heather A.; Choudhury, Atish D.; Oxnard, Geoffrey R.
Abstract: The application of genomic profiling assays using plasma circulating tumor DNA (ctDNA) is rapidly evolving in the management of patients with advanced solid tumors. Diverse plasma ctDNA technologies in both commercial and academic laboratories are in routine or emerging use. The increasing integration of such testing to inform treatment decision making by oncology clinicians has complexities and challenges but holds significant potential to substantially improve patient outcomes. In this review, the authors discuss the current role of plasma ctDNA assays in oncology care and provide an overview of ongoing research that may inform real‐world clinical applications in the near future.